Development of interfacing program using LabVIEW software / Mohd Husni On - On, Mohd Husni (2005)
This paper discuss about the application of a LabVIEW software in practical. The LabVIEW software is an industry-leading software tool for developing design, control, and test the system. In LabVIEW, we build a user interface which known as the front panel by using a set of tools and objects. We then add and generate program code using graphical representations of functions to control the front panel objects. The block diagram contains this code. Therefore, the aim of this project is to propose a program that can be used to interface with the mechatronic instrumentation. The instrument that has been used to interface is simple anemometer. In this case, Lab View software is proposed to be used as interfacing software to develop the interfacing program. The basic idea of this project is to have or get a good, smooth and ergonomic measurement and display from the results of developed instrument. To achieve this motive, the interfacing system, which uses fiber optic as a sensor, will be used.